Artificial Intelligence, Digital Crimes, and the Legal Framework for Criminal Liability in Iraq - Lafta Abdulzahra , Assist. Lect. Batool (Basra studies journal, 2026)
The Rapid advancement of artificial intelligence (AI) technologies has led to the emergence of new forms of digital crimes characterized by complexity and diversity, thereby posing unprecedented challenges to traditional criminal justice systems. This study aims to examine the relationship between artificial intelligence and digital crimes and to analyze the legal framework governing criminal liability in Iraq, with a focus on assessing the adequacy of existing legal provisions in addressing such emerging offenses. The research adopts a comparative analytical approach by exploring the fundamental concepts of artificial intelligence and digital crimes, and by identifying various forms of crimes associated with AI technologies, such as cyberattacks, digital forgery, and violations of privacy. It also analyzes the position of the Iraqi legislator under the Penal Code and related legislation. The study concludes that the Iraqi legal framework remains insufficient in regulating criminal liability arising from the use of artificial intelligence, particularly with regard to determining responsibility among users, developers, and intelligent systems themselves. Accordingly, it recommends the enactment of modern legislation that keeps pace with rapid technological developments, as well as the strengthening of international cooperation in combating AI-related cybercrimes. Moreover, the legal nature of artificial intelligence remains a subject of extensive doctrinal and legislative debate, as comparative legal scholarship has not yet reached a settled characterization of such systems due to their varying levels of autonomy and functional complexity. Some legal approaches treat AI merely as a technical tool subject to the responsibility of the user or developer, while others argue for the development of a specific legal framework tailored to the unique nature of self-learning intelligent systems. This study does not adopt a definitive position regarding the legal personality or independent legal status of artificial intelligence; rather, it focuses on analyzing the issue within the framework of existing Iraqi legislation, emphasizing the adequacy of traditional criminal rules in addressing crimes committed through such technologies.